The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.3390/ijerph191711125
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Personality and Top Management Support in Continuance Intention to Use Electronic Health Record Systems among Nurses

Abstract: This study examines nurses’ Continuance Intention (CI) to use electronic health records (EHRs) through a combination of three conceptual frameworks: the Unified Theory of Acceptance and Use of Technology (UTAUT), the theory of expectation-confirmation (ECT), and the Five-Factor Model (FFM). A model is developed to examine and predict the determinants of nurses’ CI to use EHRs, including top management support (TMS) and the FFM’s five personality domains. Data were collected from a survey of 497 nurses, which w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 144 publications
2
8
0
Order By: Relevance
“…This study explored the adoption intention theoretical model of AI-assisted diagnosis and treatment by integrating the UTAUT model and HCT theory. The findings revealed that expectancy (performance expectancy and effort expectancy) positively influenced healthcare workers’ adoption intention of AI-assisted diagnosis and treatment, corroborating well-established evidence in previous UTAUT studies [ 20 , 23 , 25 , 27 , 28 , 29 ]. Notably, effort expectancy had a relatively smaller impact in determining healthcare workers’ adoption intention of AI-assisted diagnosis and treatment compared with performance expectancy.…”
Section: Discussionsupporting
confidence: 85%
See 4 more Smart Citations
“…This study explored the adoption intention theoretical model of AI-assisted diagnosis and treatment by integrating the UTAUT model and HCT theory. The findings revealed that expectancy (performance expectancy and effort expectancy) positively influenced healthcare workers’ adoption intention of AI-assisted diagnosis and treatment, corroborating well-established evidence in previous UTAUT studies [ 20 , 23 , 25 , 27 , 28 , 29 ]. Notably, effort expectancy had a relatively smaller impact in determining healthcare workers’ adoption intention of AI-assisted diagnosis and treatment compared with performance expectancy.…”
Section: Discussionsupporting
confidence: 85%
“…First, this study enriches theoretical research on the application of medical AI scenarios. Previous research on healthcare workers’ intention to adopt technology focused on technologies such as the EHR [ 23 , 25 , 26 ], telemedicine [ 24 , 29 ], and the HIS [ 28 ]. However, limited research has been conducted on AI-assisted diagnosis and treatment.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations